PROFILE OF CARDIOPULMONARY ENDURANCE, MUSCLE STRENGTH AND FLEXIBILITY OF THE EMPLOYEES IN PT. KERETA API INDONESIA - Nova Sylviana; Raihan Shafa Nabilah; Ambrosius Purba (PAIFORI, 2021)
PT. Kereta Api Indonesia is the largest transportation company in Indonesia. To maintain company productivity, employees need good physical fitness as the components of physical fitness are cardiopulmonary endurance, good muscle strength, and flexibility. Technicians, conductors, and machinists very much need this component of good physical fitness due to the high workload. A descriptive study with a cross-sectional design was conducted on secondary data, with 163 employees from PT. KAI DAOP 1 Jakarta in May-August 2017 using the Total Sampling method. The variables measured were cardiopulmonary endurance with the Young Men's Christian Association (YMCA) bench test, muscle strength with a dynamometer, and flexibility with a pleximeter. Prevalence of the very poor category was found in cardiopulmonary endurance (35.58%), right-hand grip strength (69.33%), left-hand muscle strength (71.78%), back muscle strength (53.37%), and leg muscle strength (55.21%). However, there are also some variables dominated by the moderate category, namely push strength (39.88%), pull strength (36.2%), and interestingly flexibility showed a very good category (76.69%). It is necessary to carry out a physical fitness program with principles that are following the physical activity itself, namely the FITT principle. This is because there are components of fitness that are dominated by the very poor category, namely cardiopulmonary endurance, right-hand and left-hand muscle strength, and back and leg muscle strength. The types of exercise that can be done in the physical fitness program are moderate-intensity aerobics, walking, cycling, lifting weights, and stretching.